Development of merosporangia in Linderina pennispora (Kickxellales, Kickxellaceae) - Hussein H. El-Sheikh; Mohamed E. Zain; Steve T. Moss (IMA Fungus)
The vegetative and sporulating structures of Linderina pennispora are described using scanning and transmission electron microscopy. The vegetative hyphae and sporangiophores were regularly septate, possessed a two-layered wall, and coated with rod-shaped, 0.2-0.7 μm long, 0.15-0.25 μm wide ornamentations. The sporangiophore was erect, cylindrical, and narrower (4-8 μm) than the vegetative mycelium (8-12 μm). The mature sporocladium was ovoid to dome-shaped, sessile, non-septate, 18-24 μm diam, possessed a two-layered wall, and coated with rod-shaped ornamentations. Mature pseudophialides were ellipsoid, 2.0-2.5 μm wide, 4-7 μm long, possessed a two-layered wall, and formed in a series of concentric groups radiating from the “apex“ of the sporocladium. The pseudophialides had a round, ca. 1.5 μm diam, base with a narrower, 0.7-0.8 μm diam lobed, cylindrical neck structure in the distal region which extended to the pseudophialide neck. The merosporangia were obovate, 3-4 μm wide near the base, and narrowed distally to 2.0-2.5 μm wide, 18-23 μm long, possessed a threelayered wall, with regular surface annulation with interconnecting ridges, but lacked rod-shaped ornamentations. The merosporangia contained a single, obovate, 2.3-2.5 μm diam merosporangiospore, with a ca. 1 μm diam papilla-like base, that possessed a four-layered wall. Detached merosporangia had a single, acicular, unbranched, 3-5 μm long, ca. 0.1 μm diam “appendage“ that was attached to the merosporangiospore inner cell wall layer and passed through the septum plug to the pseudophialide.